Kieren Perkins' Left-arm Pull at 1440 m in His Gold Medal Race at the Barcelona Olympic Games (August 1992) - Rushall, B. S.
Video pictures (13 frames) and the appropriate technical/ biomechanical explanations for Kieren Perkins' Left-arm Pull at 1440 m in his gold medal race at the Barcelona Olympic Games (August 1992). There is a distinct absence of any "S-shaped" or curvilinear movement in the propulsive phase of this stroke.